2008
DOI: 10.1080/09620210802195947
|View full text |Cite
|
Sign up to set email alerts
|

Schooling and settlement: refugee education in Australia

Abstract: Schools are a stabilising feature in the unsettled lives of refugee students. They provide safe spaces for new encounters, interactions and learning opportunities. They also deliver literacy, the key to educational success, post-school options, life choices, social participation and settlement. Currently Australian schools are poorly funded and illequipped to provide effective English as a Second Language teaching and support. A new cohort of refugee students mainly from Africa and the Middle East are struggli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
147
2
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(163 citation statements)
references
References 23 publications
2
147
2
12
Order By: Relevance
“…Moreover, such an understanding must take into account refugee students' own identities and knowledge rather than assuming that refugee students can simply "fit in" to existing school environments and school cultures (Matthews, 2008; Woods, 2009). In other words, understandings of school belonging for students with refugee backgrounds must lead to a two way interaction which takes into account existing power relationships, and ensures that refugee students can feel belonging in all of the domains on their own terms as well as those of the school (Matthews, 2008;Riggs & Due, 2011; Woods, 2009).…”
Section: School Belongingmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, such an understanding must take into account refugee students' own identities and knowledge rather than assuming that refugee students can simply "fit in" to existing school environments and school cultures (Matthews, 2008; Woods, 2009). In other words, understandings of school belonging for students with refugee backgrounds must lead to a two way interaction which takes into account existing power relationships, and ensures that refugee students can feel belonging in all of the domains on their own terms as well as those of the school (Matthews, 2008;Riggs & Due, 2011; Woods, 2009).…”
Section: School Belongingmentioning
confidence: 99%
“…Specifically, their findings indicate that students reported valuing, amongst other things: the cultural diversity of their intensive language school, the presence of other students who spoke their own language, having a sense of safety and belonging, and a curriculum which allowed them to experience some success in their education. These findings indicate the importance of ensuring that the facilitation of school belonging is collaborative and reciprocal, by providing opportunities for refugee students to contribute their own knowledge and aspirations, rather than focusing school This is an Author's Accepted Manuscript of a paper published in the Educational and Developmental Psychologist Copyright Cambridge University Press DOI: 10.1017/edp.2016.9 experiences on existing school values and culture (Matthews, 2008; Woods, 2009).Finally, the literature exploring school belonging for refugee students has also found that school belonging is negatively impacted by experiences of discrimination (e.g., Brown & Chu, 2012; Trickett & Birman, 2005). Specifically, experiences of discrimination lead to a range of negative outcomes, including difficulties developing peer relationships at school, lower levels of school belonging and engagement, and decreased mental health and wellbeing (Priest et al., 2014).…”
mentioning
confidence: 99%
See 3 more Smart Citations